Comparative Analysis of the Physical Activity, Nutrition and Health Behaviour in Physical Education Students: Gender Differences - Popović Jasna; Popović Miloš; Popović Ružena (Britain International for Academic Research (BIAR) Publisher, 2020)
A question that has interested physical activity researches in recent years is whether involvement in Physical Activity (PA) is associated with the adoption of other health behaviours, such as good nutrition and no smoking. In this pilot study was implemented the complex Diet Questionnaire, on PA, Health, Nutrition, within the group of the healthy adults, specifically selected students of the Faculty of Sport and PE (in Total 74 respondents). Applied Q contains 7 segments (23 items) dealing with: Medical and Social status, Body mass, and Body High, Nutrition, Physical Activity, and Life Style. Study results are presented as comparative analysis of gender differences. Applied variables within (1–7) segments have non parametric properties. The proposed health outcomes suggest that considerable public health benefits could be achieved through PA. The identification of PA patterns is important if any effort to plan public health initiatives in this field.